In the shadow of violence : politics, economics, and the problem of development - North, Douglass C. (Douglass Cecil).; Wallis, John Joseph; Webb, Steven Benjamin, 1947-; Weingast, Barry R. (Cambridge : Cambridge University Press, 2013)
'This book applies the conceptual framework of Douglass C. North, John Joseph Wallis and Barry R. Weingast's Violence and Social Orders (Cambridge University Press, 2009) to nine developing countries. The cases show how political control of economic privileges is used to limit violence and coordinate coalitions of powerful organizations. Rather than castigating politicians and elites as simply corrupt, the case studies illustrate why development is so difficult to achieve in societies where the role of economic organizations is manipulated to provide political balance and stability. The volume develops the idea of limited-access social order as a dynamic social system in which violence is constantly a threat and political and economic outcomes result from the need to control violence rather than promoting economic growth or political rights'--
Includes bibliographical references and index.
Keywords: Developing countries -- Economic conditions; Developing countries -- Social conditions